The Association of Pathology Chairs' Pathology Leadership Academy: Experience From the First 2 Years - Lydia Pleotis Howell MD; Priscilla S. Markwood CAE; Dani S. Zander MD (Elsevier, 2019)
Leadership development and succession planning are critical to ensure continued strength of academic pathology. The Association of Pathology Chairs developed the Pathology Leadership Academy to prepare future academic leaders. The purpose of this report is to describe: (1) Pathology Leadership Academy's development and curriculum, (2) how Pathology Leadership Academy has met leadership development needs for individuals and academic departments in its first 2 years, (3) Pathology Leadership Academy's future directions based on program feedback. Results were analyzed from pre- and postprogram needs assessment surveys of pathology chairs and from evaluations from Pathology Leadership Academy participants in the first 2 years. Pathology Leadership Academy curriculum was developed from topics identified as priorities in the chairs' survey. Twenty-eight (90%) of 31 responding participants were very satisfied/satisfied with Pathology Leadership Academy. Of the 18 responding chairs who sent a participant to Pathology Leadership Academy, 11 (61%) reported that Pathology Leadership Academy met their faculty development goal. Of all responding chairs, 13 (32%) of 41 reported uncertainty as to whether Pathology Leadership Academy is meeting chairs' goals. Chairs reported that Pathology Leadership Academy provided value to their faculty through preparation for a future leadership role, enhancing skills for a current role, and enhancing understanding of opportunities and challenges in academic medicine. Most chairs (27/43, 66%) said Pathology Leadership Academy should be offered again; 13 (32%) of 43 were uncertain, and 1 (2%) of 43 said no. Initial experience of Pathology Leadership Academy is positive and promising and provides opportunity for leadership succession planning in academic pathology. Pathology Leadership Academy will use participant and chair feedback for ongoing curricular development to ensure topics continue to address major needs of academic pathology.